Funcionamiento familiar y autocuidado en adultos sometidos a hemodiálisis, Hospital Víctor Lazarte Echegaray-Essalud - Goicochea Castillo, Cynthia Lizbet (2020)
The present research study, of a quantitative-descriptive correlational cross-sectional type, was carried out in the hemodialysis unit of the Víctor Lazarte Echegaray-Essalud Hospital, was performed in the Hemodialysis Unit of the Hospital Víctor Lazarte Echegaray-Essalud, in order to establish the relationship between family functioning and self-care level in adults undergoing hemodialysis. The sample consisted of 70 adults who met the inclusion criteria. For the data collection, the Family Function Test FF-SIL was used, as well as the Questionnaire for the assessment of the self-care level of the alterations of the patient's health in hemodialysis treatment, modified by the author. The information was processed in the IBM SPSS STATISTICS Version 23 statistical program. It was concluded: The highest percentage (47.1%) of the adults undergoing hemodialysis, presented family functioning level: moderately functional, 34.3% functional, 11.4% dysfunctional and 7.1% severely dysfunctional. The highest percentage (78.6%) of the adults undergoing hemodialysis, their self-care is adequate and 21.4% inadequate self-care and there is a significant relationship between the level of family functioning and the level of self-care in adults undergoing hemodialysis; chi square of 48,600 with probability 0.000 being highly significant.